PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN PROMOSI TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MODERASI (Studi Pada Konsumen Larissa Aesthetic Center Solo) - Retno Wulandari, Suprihatmi Sri Wardiningsih & Erni Widajanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
The purpose of this research was: 1) to analyze the significance of the influence of the quality of products against customer satisfaction. 2) to analyze the significance of the influence of the quality of service of consumer satisfaction. 3) to analyze the significance of the influence of promotions against consumer satisfaction. 4) to analyze the significance of the influence of consumer satisfaction consumer loyalty against. 5) to analyse the influence of the quality of products consumer loyalty against Larissa Aesthetic Center Solo satisfaction in moderation. 6) to analyse the influence of the quality of service of consumer loyalty satisfaction in moderation. 7) to analyze the influence of consumer loyalty promotion against Larissa Aesthetic Center Solo satisfaction in moderation. Research methods method using survey data, the type of data used was qualitative and quantitative data, the data sources used are primary data and secondary data. The population in this research is that consumers do care at the Larissa Aesthetic Center. Sampling techniques in the research of using proportional cluster random sampling, the number of samples that used as many as 60 respondents. Methods of data collection were used: questionnaire and documentation. Technique of data analysis used the test of validity, reliability test, test the assumptions of classical, linear multiple regression test, t-test, F-test (test of the Model Ordinance), the coefficient of determination, and absolute difference test. The research results obtained conclusions: 1) there is a significant influence on the quality of products consumer loyalty against Larissa Aesthetic Center. 2) there is a significant influence on the quality of service of consumer loyalty Larissa Aesthetic Center. 3) there is a significant influence on the promotion of consumer loyalty against Larissa Aesthetic Center. 4) there is a significant influence of the influential consumer satisfaction significantly to consumer loyalty Larissa Aesthetic Center. 5) consumer satisfaction is not moderating influence product quality consumer loyalty against Larissa Aesthetic Center. 6) influence of moderate satisfaction service quality against consumer loyalty Larissa Aesthetic Center. Consumer satisfaction is not moderating influence promotion of consumer loyalty against Larissa Aesthetic Center.Keywords: product quality, quality of service, promotion, consumer loyalty, satisfaction of consumers.